Publicar primeiro, verificar depois?: uma reflexão sobre a credibilidade do jornalismo e o papel das organizações de verificação de fatos - Morais, Ricardo (2023)
In the current media ecology where we witness the breaking down of barriers between producers, consumers and disseminators of information, we are also faced with the awakening of the phenomenon of fake news. A phenomenon, which, as we know, is not new, since false reports, rumours and distortions are practically as old as the history of media and journalism). In the present article we bring a reflection on the construction and decline of journalistic credibility in this context of information abundance and the role of inversion in the news production process - in which fact-checking is done after publication. Through the analysis of how fact-checking organizations are built, we question the need to create external projects in place of an internal bet, recovering the traditional fact-checkers that guaranteed the accuracy of contents before their publication.